Challenges of PMTCT and MCHS Integration in Indonesia, Analysis by Integration Analysis Framework and CFIR - Wiraharja, Regina Satya; Trisnantoro, Laksono; Mahendradhata, Yodi; Praptoharjo, Ignatius (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
Integration was strategy of PMTCT (Prevention of Mother to Child HIV Transmission) and MCHS (Mother and Child Health Services) since 2006. This systematic review explored integration level between PMTCT and MCHS. Literature searched from June 2015 to January 2016 through Google, Google Scholar, University Library Website, Portal Garuda, ProQuest, PubMed and 90 institutions in Jakarta. Keywords were PMTCT, HIV Mother, PPIA HIV Evaluation and HIV PMTCT Evaluation. We yielded 157 literatures from 1995-2015. Research should be done at Public Primary Health Care (PHC), discussed PMTCT implementation, and captured perspectives of staffs or decision makers. Thematic analysis was done using Atun’s Integration Analysis Framework and CFIR. We included 7 studies. No study explored overall dimensions of integration, especially planning function. Challenges were resources, execution, needs of patients, networks and communications, policies, leadership, and access to information. Only 4 studies showed PMTCT results. Coverage of first visit counseling was 9-100% and percentage of pregnant women tested was 3.9 -60%. PMTCT integration was partial. Integration was not a sole solution to results. Planning should be done together with regional and local level, involving stakeholders to disseminate PMTCT information, increasing ownership and leadership. We proposed Atun’s Framework and CFIR for further research.